2007
DOI: 10.1002/cbm.647
|View full text |Cite
|
Sign up to set email alerts
|

The effect of rugby match outcome on spectator aggression and intention to drink alcohol

Abstract: This study suggests that team success but not failure may increase aggression among supporters, and that aggression, not celebration, drives post-match alcohol consumption. Losing and drawing decreased happiness but winning did not increase it. Better understanding of pathways to violence in these circumstances will pave the way for more effective prevention and management strategies.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
19
0
3

Year Published

2008
2008
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(24 citation statements)
references
References 21 publications
2
19
0
3
Order By: Relevance
“…In short, although one's environs feel stabilized, complete and ever-lasting, they are more problematic than this as they are infused with the experience of outside and inside bodily functions and cartographies. Being drunk or tipsy changes our interpretation of the self, loosens our inhibitions and leads us to make unwise choices (Moore, Shepherd, Eden, & Sivarajasingam, 2007). Spaces of drinking are therefore encountered in and through embodiment (sensations), in and through practices (drinking, dancing, talking, etc.…”
Section: Resisting Masculinities? Young Women Who Drinkmentioning
confidence: 99%
“…In short, although one's environs feel stabilized, complete and ever-lasting, they are more problematic than this as they are infused with the experience of outside and inside bodily functions and cartographies. Being drunk or tipsy changes our interpretation of the self, loosens our inhibitions and leads us to make unwise choices (Moore, Shepherd, Eden, & Sivarajasingam, 2007). Spaces of drinking are therefore encountered in and through embodiment (sensations), in and through practices (drinking, dancing, talking, etc.…”
Section: Resisting Masculinities? Young Women Who Drinkmentioning
confidence: 99%
“…This may be particularly problematic at schools in which the football program is highly emphasized and/or successful. Indeed, one study of rugby spectators showed that post-game alcohol consumption is associated with aggression (not celebration), but that team success may increase aggression among fans (Moore et al, 2007). Another study demonstrated that students’ self-reported alcohol consumption on football game days paralleled their self-reported alcohol consumption on holidays (Neal & Fromme, 2007).…”
Section: Introductionmentioning
confidence: 99%
“…23,24 Our study results are consistent with studies that link sporting events with violence. [1][2][3][4][5][6][7] Football games were associated with increased homicide rates in Cali and the strength of this association was even higher when football games were played at home. Interestingly, the outcome of the game was not associated with interpersonal violence deaths in our study.…”
Section: Discussionmentioning
confidence: 99%
“…Late-night alcohol drinking and violence commonly occur after football events. 1,5,22 This could affect the incidence of homicides the day after football; these days were indicated and included in the analyses. In addition, we accounted for an overall trend during 2005 to 2008 by including two fractional polynomials, and we accounted for seasonality by including a sine-cosine pair with annual periodicity.…”
Section: Statistical Analysesmentioning
confidence: 99%